A new species and new records of Tachygerris Drake, 1957 (Hemiptera: Heteroptera: Gerridae) from Colombia - Morales-C., Irina T.; Castro-Vargas, Maria I. (Zootaxa, 2013)
A new species of the genus Tachygerris Drake, 1957 (Gerrinae: Tachygerrini) is described from the Amazon region of Colombia. Tachygerris tucanensis sp. nov. is differentiated from other species of the genus by features of the male geni-talia and of last abdominal sternite of female. New records of T. adamsoni, T. celocis, and T. opacus are also presented.